Europa - Pappalardo, Robert T.; McKinnon, William B.; Khurana, K. (University of Arizona space science series., 2009)
"Few worlds are as tantalizing and enigmatic as Europa, whose complex icy surface intimates the presence of an ocean below. Europa beckons for our understanding and future exploration, enticing us with the possibilities of a water-rich environment and the potential for life beyond Earth. This new volume in the Space Science Series, with more than 80 contributing authors, reveals the discovery and current understanding of Europa's icy shell, subsurface ocean, presumably active interior, and myriad inherent interactions within the Jupiter environment. Europa is the foundation upon which the coming decades of scientific advancement and exploration of this world will be built, making it indispensable for researchers, students, and all who hold a passion for exploration."--Jacket.